2021
DOI: 10.1590/s1980-220x2020001803708
|View full text |Cite
|
Sign up to set email alerts
|

Problem-solving and coping in family adaptation of children with Down Syndrome

Abstract: Objective: To analyze problem-solving and coping strategies of parents of children with Down Syndrome in family adaptation. Method: This is a qualitative research that used the Resiliency Model of Family Stress, Adjustment, and Adaptation. Participants were mothers and/or fathers from 40 families of children aged 1 to 7 years diagnosed with DS. Directed content analysis was performed, supported by software and considering a code dictionary. Results: Problem-solving and coping proved to be a set of actions, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 21 publications
1
19
0
11
Order By: Relevance
“… 2020 ; Braga et al . 2021 ). It appears that parenthood involves experiential and hormonal changes that influence the hippocampus and prefrontal cortex, which are brain areas involved in cognition and mood regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2020 ; Braga et al . 2021 ). It appears that parenthood involves experiential and hormonal changes that influence the hippocampus and prefrontal cortex, which are brain areas involved in cognition and mood regulation.…”
Section: Discussionmentioning
confidence: 99%
“… 2020 ; Sarimski 2020 ; Braga et al . 2021 ) argue that parents of children with Down syndrome offer the greatest opportunities to facilitate their children's learning and development, although they are not being active participants in the intervention. During massage, babies can receive integrated information from their caregiver through different sensory channels and can focus their attention on these complex stimulations to learn and adapt to the environment (Purpura et al .…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study conducted with parents of children with DS, between one to seven, years old, showed that belief in God was referred to by the participants as a resource for them to adapt to the fact of caring for a child with DS [ 29 ]. Other studies conducted with children with chronic conditions also showed faith in God as a support in times of difficulty and support to cope with the demands arising from health problems [ 11 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a qualitative secondary analysis (QSA) of the research project “Family and individual adjustment in Brazilian families living with children and adolescents with Down Syndrome” [ 29 , 30 , 31 , 32 ]. The QSA refers to using existing data collected for a different research work [ 33 ], allowing a new perspective or look at the original data.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, family problem-solving and coping can affect support and resources as perceived by the family. Over time, it causes changes in family functions and the relationship between the family and the outside world ( 29 ). Zhang et al ( 30 ) pointed out that social support is a key factor affecting family functioning.…”
Section: Introductionmentioning
confidence: 99%